4(6-3v)=96

Simple and best practice solution for 4(6-3v)=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6-3v)=96 equation:


Simplifying
4(6 + -3v) = 96
(6 * 4 + -3v * 4) = 96
(24 + -12v) = 96

Solving
24 + -12v = 96

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -12v = 96 + -24

Combine like terms: 24 + -24 = 0
0 + -12v = 96 + -24
-12v = 96 + -24

Combine like terms: 96 + -24 = 72
-12v = 72

Divide each side by '-12'.
v = -6

Simplifying
v = -6

See similar equations:

| 12m+5n-3m+10n= | | 160+.15m=241 | | 7x+117=-6x | | log[2]3x-6=4 | | -6x-3=3-6y | | 7x-35+3=6x-42 | | (x-6)-7=-3 | | 12p+19q+p-6q-3p= | | 1+x+2=3+x+4 | | 4(x+2)=30+3x | | X^2lnx-4lnx=0 | | 6a=80-4d | | 8x+10=8x-9 | | X^2=220+5 | | x^2+5x-3=3x+5 | | x^2+16x-15=0 | | 17=(-13)-(8x) | | 21-15=3(x-7) | | 15a+14b+6c+5c-5b-5a= | | 2x+7y+z=29 | | 4x-2(x-3)=-2+5x-4 | | 6x-3x=7 | | 50=47+12+4w | | -5(x)+23=-7 | | 3x+2y+z=17 | | 6r+2(r+6)=4r+12 | | 12+4x=-2x-9 | | 3y+8x+3=14+8x | | x^2-6x+4=-9x+2 | | 3=0.5+11 | | 2x+5+110= | | 2x+4=2x+2(x+2) |

Equations solver categories